2022
DOI: 10.1111/ejh.13771
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism parameters and their relation to cytogenetics in multiple myeloma

Abstract: Objectives Our aim was to correlate serum levels of selected markers of bone metabolism and bone marrow microenvironment to cytogenetic changes in patients with multiple myeloma (MM). Methods We assed cytogenetic changes in 308 patients and correlated them with the following levels of bone marrow metabolism: thymidine kinase (TK), β2‐microglobulin (b‐2‐m), Dickkopf‐1 protein (DKK‐1), C‐terminal telopeptide collagen‐I (ICTP), N‐terminal propeptide of type I procollagen (PINP), receptor for interleukin 6 (rIL‐6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The aforementioned study found that progressive clonal expansion was a feature of 17.5% 1q gain cases, whereby 1q gain at diagnosis evolved into 1q amplification at relapse. Compared with normal 1q + , 1q + from presentation and evolution of new gain (1q + ) at relapse were both associated with significantly shorter OS (HR, 2.11; P=0.0040; and HR, 2.00; P=0.021, respectively) (71).…”
Section: Treatment Of MM Patients With 1q21 +mentioning
confidence: 98%
See 1 more Smart Citation
“…The aforementioned study found that progressive clonal expansion was a feature of 17.5% 1q gain cases, whereby 1q gain at diagnosis evolved into 1q amplification at relapse. Compared with normal 1q + , 1q + from presentation and evolution of new gain (1q + ) at relapse were both associated with significantly shorter OS (HR, 2.11; P=0.0040; and HR, 2.00; P=0.021, respectively) (71).…”
Section: Treatment Of MM Patients With 1q21 +mentioning
confidence: 98%
“…Osteopathy, such as myeloma, is present in >80% of patients with MM at diagnosis, which ranges from osteoporosis to typical lytic lesions, and then to advanced lesions such as structural bone defects or pathological fractures (70). In a retrospective study of 308 patients with MM, the presence of 1q21 gain was associated with a higher level of thymidine kinase (TK) (P=0.026) and a lower level of amino-terminal propeptide of type I procollagen (PINP) (P=0.030) (71). Among them, TK is a cell proliferation marker.…”
Section: Pathogenesis and Clinicopathological Features Of 1q21 + In P...mentioning
confidence: 99%
“…The efficacy of urinalysis in monitoring patients with MM is limited by factors such as limited analytical sensitivity, influence of renal metabolism, and inadequate supply of urine samples. [25] (3) Bone marrow analysis: The occurrence and advancement of hematological tumors are followed by changes in the surrounding tissue microenvironment, [26,27] including both hematopoietic and non-hematopoietic cells, along with non-cellular constituents. [28] Bone marrow examination revealed the presence of proliferating myeloma cells.…”
Section: Laboratory Examinationmentioning
confidence: 99%
“…(3) Bone marrow analysis: The occurrence and advancement of hematological tumors are followed by changes in the surrounding tissue microenvironment, [ 26 , 27 ] including both hematopoietic and non-hematopoietic cells, along with non-cellular constituents. [ 28 ] Bone marrow examination revealed the presence of proliferating myeloma cells.…”
Section: Laboratory Examinationmentioning
confidence: 99%